When the Puppet Becomes Human: The Gothic Posthumanism of In the Lives of Puppets (2023) - González, Esther Muñoz (Complutense Journal of English Studies, 2025)
In the Lives of Puppets (2023) reinterprets Carlo Collodi’s Pinocchio set in a dystopian future where most of humanity has disappeared. Victor Lawson is a 19-year-old human who lives peacefully with his unconventional family of non-human machines. Their tranquil life in an isolated wood is shattered when Victor finds and repairs an android, Hap, and unintentionally reveals the family’s location to the dangerous robots from the City of Electric Dreams. This paper discusses In the Lives of Puppets through the lenses of posthumanism, Affect theory, and Gothic fiction. Drawing on Rosi Braidotti’s view that posthuman subjects are relational entities defined by connections with both human and nonhuman agents, the story challenges the traditional boundaries of identity. Affect theory emphasizes the fluidity of relationships and emotions, challenging notions of human superiority and suggesting that emotions can transcend human experience. The novel’s connection to Gothic fiction’s exploration of societal anxieties further develops this analysis. Through its depiction of fears related to biotechnological advancement, In the Lives of Puppets reflects contemporary concerns about identity and agency in a machine-dominated world. Ultimately, the novel